National Trends and Factors Associated With Inpatient Mortality in Adult Patients With Opioid Overdose. (January 2019) - Burton, Brittany N.; Lin, Timothy C.; Said, Engy T.; Gabriel, Rodney A.
Abstract : BACKGROUND: The prevalence of opioid misuse and opioid-related mortality has increased dramatically over the past decade. There is limited evidence on factors associated with mortality from opioid overdose in the inpatient setting. The primary objective was to report national trends in opioid overdose and mortality. The secondary objectives were to explore factors associated with inpatient mortality and report differences in prescription opioid overdose (POD) versus illicit opioid overdose (IOD) cohorts. METHODS: Using the 2010–2014 Nationwide Inpatient Sample, we performed a cross-sectional analysis and identified a weighted estimate of 570, 987 adult patients with an International Classification of Disease, Ninth Revision, or External Cause of Injury code of POD or IOD. We performed multivariable logistic regression to identify predictors of inpatient mortality. The odds ratio (OR) and their associated 95% confidence interval (CI) are reported. RESULTS: Of the 570, 987 patients with opioid overdose, 13.8% had an admissions diagnosis of IOD, and the remaining had POD. Among all opioid overdose admissions, the adjusted odds of IOD admissions increased by 31% per year (OR, 1.31; 95% CI, 1.29–1.31; P < .001); however, the adjusted odds POD admissions decreased by 24% per year (OR, 0.76; 95% CI, 0.75–0.77; P < .001). The mortality was 4.7% and 2.3% among IOD and POD admissions, respectively. The odds of inpatient mortality increased by 8% per year among IOD admissions (OR, 1.08; 95% CI, 1.02–1.14; P < .007). The odds of inpatient mortality increased by 6% per year among all POD admissions (OR, 1.06; 95% CI, 1.03–1.09; P < .001). Those with IOD compared to POD had higher odds of mortality (OR, 2.03; 95% CI, 1.79–2.29; P < .001). Patients with age ≥80 years of age and those with a diagnosis of a solid tumor malignancy had higher odds of mortality. Odds of inpatient mortality were decreased in African American versus Caucasian patients and in patients undergoing alcohol rehabilitation therapy. CONCLUSIONS: The increase in mortality provides a strong basis for further risk reduction strategies and intervention program implementation. Medical management of not only the opioid overdose but also the comorbidities calls for a multidisciplinary approach that involves policy makers and health care teams.